Expression of galectin-9 mRNA in obese children with polymorphism of the lactase gene - A.E. Abaturov; V.E. Dosenko; A.A. Nikulina (Zaslavsky O.Yu., 2018)
Background. The aim of the study is to investigate the association of expression of galectin-9 (Gal-9) mRNA and lactose malabsorption in obese children with polymorphism (SNP) of the lactase gene (LCT) and to study the efficacy of lactase deficiency therapy using exogenous lactase preparations. Materials and methods. Seventy obese children (BMI > 95th percentile) and 16 children without obesity aged 6-18 years were examined. There was studied SNP LCT (material for investigation venous blood) by real-time PCR, expression of Gal-9 mRNA (study material buccal epithelium) by real-time PCR with reverse transcription, malabsorption of lactose by hydrogen breath test (HBT). Among obese children, 38 children with genotype C/C 13910 presented the first observation group, 32 children with phenotype identical genotypes C/T 13910 and T/T 13910, p > 0.05, presented the second group. Children from the first observation group also determined the level of expression of Gal-9 mRNA and lactose malabsorption after using exogenous lactase preparations. Results. The genotype C/C 13910 was determined in 38 (54.3 %), genotype C/T 13910 in 22 (31.4 %) and genotype T/T in 10 (14.3 %) patients. Malabsorption of lactose in children with genotype C/C 13910 averaged 32.7 ± 10.4 pmm, in children with genotypes C/T 13910 - 26.3 ± 4.9 pmm (p > 0.05) and with genotype T/T 13910 and was absent in children without obesity (p < 0.05). The average level of expression of Gal-9 mRNA in children with genotype C/C 13910 was 564.3 ± 32.8 RU DmRNA Gal-9/mRNA actin, in children with genotypes C/T and T/T 13910 - 61.04 ± 15.30 RU DmRNA Gal-9/mRNA actin, p < 0.01. It is of great importance that the children with genotype C/C 13910 and lactose malabsorption (n = 20) had the lowest average level of expression of Gal-9 mRNA (42.47 ± 13.30 RU DmRNA Gal-9/mRNA actin) whereas the children with genotype C/C 13910 and without lactose malabsorption (n =18) had the largest level (1086.73 ± 52.60 RU DmRNA Gal-9/mRNA actin), which exceeded the expression level of Gal-9 mRNA in children without obesity and lactose malabsorption (313.34 ± 19.70 RU DmRNA Gal-9 / mRNA actin), p < 0.01. After the use of exogenous lactase preparations in children with genotype C/C 13910 and lactose malabsorption for a month, the level of expression of Gal-9 mRNA approximated to the level of 246.21 ± 15.70 RU DmRNA Gal-9/mRNA actin, whereas when used only the low-lactose diet the level increased insignificantly to 58.72 ± 21.10 VD DmRNA Gal-9/mRNA actin, p < 0.01. It is also interesting that in children with genotype C/C 13910 without lactose malabsorption against the background of a low-lactose diet, the level of expression of Gal-9 mRNA decreased to 388.38 ± 20.40 RU DmRNA Gal-9/mRNA actin, approaching the level of healthy children without obesity. Conclusions. In children with genotype C/C 13910 the level of expression of Gal-9 mRNA depends on the lactose malabsorption, which requires replacement therapy that combines a low-lactose diet and the use of exogenous lactase preparations. In the absence of lactose malabsorption, using only the low-lactose diet in children with genotype C/C 13910 approximates the level of expression of Gal-9 mRNA to the level of healthy children without obesity.